2020
DOI: 10.1002/nano.202000009
|View full text |Cite
|
Sign up to set email alerts
|

Poly(maleic anhydride) copolymers‐based polymer electrolytes enlighten highly safe and high‐energy‐density lithium metal batteries: Advances and prospects

Abstract: Polymer electrolytes‐based lithium metal batteries have attracted much more attention for next‐generation energy storage devices owing to their high energy density and superior safety characteristics. However, there are still some obstacles to ameliorate interfacial compatibility between conventional polymer electrolytes with lithium metal anode and high‐voltage cathodes. It is noted that poly (maleic anhydride) copolymers (PMAC)‐based polymer electrolytes (PEs) exhibit superior interfacial compatibility with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…MA promotes the synthesis of poly(maleic anhydride)‐copolymer, through the free radical polymer. Then, it can act as graft sites for amidation and esterification reactions to design anhydride polymers with different side chains [19,71] . Especially, polymethyl methacrylate (PMMA) regulation is a suitable polymer‐based solid electrolyte for the adverse reaction of the lithium‐mental electrode and with a higher lithium ion migration number [72,73] .…”
Section: Fundamentals Of Polymer Materials For Solid‐state Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…MA promotes the synthesis of poly(maleic anhydride)‐copolymer, through the free radical polymer. Then, it can act as graft sites for amidation and esterification reactions to design anhydride polymers with different side chains [19,71] . Especially, polymethyl methacrylate (PMMA) regulation is a suitable polymer‐based solid electrolyte for the adverse reaction of the lithium‐mental electrode and with a higher lithium ion migration number [72,73] .…”
Section: Fundamentals Of Polymer Materials For Solid‐state Electrolytesmentioning
confidence: 99%
“…4) Safety: suppression of dendrites and thermal runaways. [14,15] Here, several polymer electrolyte materials, such as polyethylene oxide (PEO), [16] polyacrylonitrile (PAN), [17] polyvinylidene fluoride (PVDF), [18] and poly(maleic anhydride) (PMMA), [19] were selected to elaborate the connection between electrolyte structures and intrinsic properties. Meanwhile, the corresponding optimization strategies for SPEs with different structures were systematically summarized to boost their application in ASSBs (Table 1).…”
Section: Fundamentals Of Polymer Materials For Solid-state Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various inorganic oxides have been applied as inert fillers for PEO-based electrolytes, such as, Al 2 O 3 [27,60,61] and Ti n O 2nÀ1 (n = 1, 2) [28]. Oxide nanoparticles acts as the role of a Lewis acid can associate with oxygen atoms in PEO chains, which reduces crystallization of the PEO and weakens interaction between the polymer and Li ions, thus, leading to the improvement of ionic conductivity [62]. For one study, Liang and co-workers [29] employed SiO 2 as filler to prepared Li-S batteries showed excellent cycling performance with a reversible discharge capacity of about 800 mAh g À1 after 25 cycles.…”
Section: Peo-based Electrolytementioning
confidence: 99%
“…Specifically, the lithophilic environment generated by abundant electron-rich groups in MHPP promotes the ionization of lithium salts, leading to an increased carrier concentration . In addition, the steric effect of MAH and HFBMA hinders the crystallization of the PEO matrix, thereby increasing the amorphous regions for better ion conduction . Furthermore, the high mobility of PEGMA and PEGDA accelerates the movement of Li + ions along their repeated EO units .…”
mentioning
confidence: 99%